Pengaruh Komitmen Organisasi Terhadap Kinerja Karyawan pada PT. KAF Media Nusantara Cabang Kab. Bangkalan - Fitri Amelia; Hikmatul Ilmi; Qurrota A’yun; Iriani Ismail (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study focuses on determining the effect of organizational commitment on employee performance at PT. KAF Media Nusantara, Bangkalan Regency Branch. In this study, Organizational Commitment is divided into 3 parts: Affective Organizational Commitment, Sustainable Organizational Commitment and Normative Organizational Commitment. This study uses qualitative. Data were collected through in-depth interviews. This study aims to explore that organizational culture and internal communication are factors in how factors in an organization can affect individual performance in the workplace. The results of the study indicate that organizational commitment has a positive effect on employee performance. The findings of this study can contribute to the development of human resources, especially at PT. KAF Media Nusantara, Bangkalan Regency Branch.